Sickle cell disease in Western Nepal - Pande, Rajan; Ghimire, Pragya Gautam; Chand, Priyankar Bahadur; Gupta, Sharmila (Nepal Journal of Medical Sciences, 2019)
Introduction: Since 2003, only few cases of sickle cell disease have officially been reported in Nepalese medical journals, and all reported patients belong to the Tharu ethnic group of Nepal. This is the first study that details sickle cell disease and carrier in 1250 individuals in western Nepal. Methods: This is a retrospective review of the patients and carriers of sickle cell disease diagnosed by either a positive haemoglobin electrophoresis report or a positive high performance liquid chromatography (HPLC) report. Analysis was done using SPSS 20. Results: Out of the 1250 individuals, 51.4% were females. 601 (48.08%) were patients with a form of sickle cell disease, the mean age was 24.5  12 yrs years. Most patients came from Bardiya district. Most common symptoms were related to joint pain. The patients and carriers of sickle cell disease were mostly from Tharu ethnic group (97.7%). Conclusion: These data suggest that sickle cell disease and other haemoglobinopathies are more prevalent than previously reported among members of the Tharu ethnic group and other residents of western Nepal. More research is imperative to assess the burden of the sickle cell disease and other haemoglobinopathies in Nepal.